Perinatal and Maternal Outcomes in Two Groups of Normal and At the Risk of Borderline Oligohydramnios in Late Preterm Pregnancy - Hassan, Saddiqa; Ali, Sana; Sherazi, Sajid Hussain (International Journal of Applied Sciences and Biotechnology, 2020)
Background: Pregnancy outcomes of a borderline oligohydramnios versus normal relatively comes to be slightly increasing meconium‐stained fluid, low Apgar scores and hyper bilirubinemia on follow up as perinatal outcomes and increased risk of C section as maternal outcome. There is currently insufficient evidence to recommend additional perinatal and maternal testing based on a borderline oligohydramnios. Clinical determination is considered in evaluating meconium‐stained fluid, low Apgar scores and hyper bilirubinemia. Objective: The purpose of this study is to determine the adverse perinatal and maternal outcomes in uncomplicated late preterm pregnancies with borderline oligohydramnios. Setting: A total of 38 patients were studied, 19 were with normal AFI and 19 patients were of borderline AFI. Patients with normal AFI were referred as Group 1 and the other as Group 2. This study was conducted at Niazi Medical and Dental College, Sargodha. Population: Pregnant women with normal AFI at term and borderline patients with late preterm pregnancy and borderline oligohydramnios. Methods: This descriptive study was conducted at Niazi Medical and Dental College, Sargodha. This study comprised of 38 patients with normal AFI and border line AFI. Data of 19 patients with normal AFI and 19 patients with border line AFI was collected. The Inclusion Criteria was 19 singleton pregnancies of 36+6 weeks, with AFI ≤ 8 cm and 19 singleton pregnancy 37+ weeks with upto 24 cm AFI. In both groups, Maternal and perinatal outcomes were assessed. The results of both groups were compared in the end. Conclusion: The results of this study indicated that borderline AFI was not a risk for adverse perinatal and maternal outcomes in uncomplicated, late preterm pregnancies. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 29-32